Mature dendritic cells enriched in regulatory molecules may control regulatory T cells and the prognosis of head and neck cancer - Minohara, Kiyoshi; Imai, Masaki; Matoba, Takuma; Wing, James Badger; Shime, Hiroaki; Odanaka, Mizuyu; Uraki, Ryuta; Kawakita, Daisuke; Toyama, Tatsuya; Takahashi, Satoru; Morita, Akimichi; Murakami, Shingo; et al. (Cancer science, 2023)
We previously reported that regulatory T (Treg) cells expressing CTLA‐4 on the cell surface are abundant in head and neck squamous cell carcinoma (HNSCC). The role of expanded Treg cells in the tumor microenvironment of HNSCC remains unclear. In this study, we reveal that the tumor microenvironment of HNSCC is characterized by the high expression of genes related to Treg cells, dendritic cells (DCs), and interleukin (IL)‐17‐related molecules. Increased expression of IL17A, IL17F, or IL23A contributes to a favorable prognosis of HNSCC. In the tumor microenvironment of HNSCC, IL23A and IL12B are expressed in mature dendritic cells enriched in regulatory molecules (mregDCs). The mregDCs in HNSCC are a migratory and mature phenotype; their signature genes strongly correlate with Treg signature genes in HNSCC. We also observed that IL17A was highly expressed in Th17 cells and exhausted CD8+ T cells in HNSCC. These data suggest that mregDCs in HNSCC may contribute to the prognosis by balancing Treg cells and effector T cells that produce IL‐17. Targeting mregDCs may be a novel strategy for developing new immune therapies against HNSCC. The tumor microenvironment of head and neck squamous cell carcinoma (HNSCC) is enriched with regulatory T (Treg) cells. Here, we report an association between Treg cells and mature dendritic cells enriched in regulatory molecules (mregDCs) expressing IL23A in HNSCC. IL23A+ mregDCs may control the balance between Treg and interleukin‐17‐producing effector T cells and contribute to HNSCC prognosis.